Biodegradation of dibutyl phthalate by a novel endophytic Bacillus subtilis strain HB-T2 under in-vitro and in-vivo conditions. Issue 13 (7th June 2022) - Xu, Wen-Jun; Wan, Qun; Wang, Wen-Feng; Wang, Ya; Feng, Fa-yun; Cheng, Jin-Jin; Yuan, Jian-Jun; Yu, Xiang-Yang
ABSTRACT: The environmental prevalence and potential toxicity of dibutyl phthalate (DBP) motivate the attempt to develop feasible strategies to deal with DBP contamination. In this study, a strain of endphytic bacteria HB-T2 was isolated from sorrel roots and identified as Bacillus sp. by analysing its morphology, physiology, biochemistry and 16S rDNA sequence. The degradation efficiency of DBP by HB-T2 was almost identical under the temperature of 30∼40°C, but was significantly enhanced as the culture pH and inoculum size increases from 6.0 to 8.0, and 1% to 5% respectively. The degradation kinetics of DBP could be well described by the first-order kinetic model, with the degradation half-life ranging from 1.59 to 7.61 h when the initial concentrations of DBP were in the range of 5–20 mg/L. LC-MS analysis of the culture samples taken at varying intervals revealed monobutyl phthalate, phthalic acid and protocatechuic acid as the major metabolic intermediates during the degradation process. HB-T2 exhibited an excellent capability to degrade a wide range of phthalate esters (PAEs), especially butyl benzyl phthalate (BBP), dipentyl phthalate (DPP), and diisobutyl phthalate (DIBP). Inoculation of HB-T2 into Chinese cabbage ( Brassica chinensis L.) growing in DBP-contaminated soils could significantly reduce the DBP levels in plant tissues and relieve the phytotoxic effects of DBP. Results of this study highlighted the great potential of this novel endophytic Bacillus subtilis strain HB-T2 for bioremediation of PAEs contamination and improvement of agricultural product safety by reducing PAEs accumulation in edible crops. GRAPHICAL ABSTRACT: UF0001